Quorum sensing and quorum quenching studies in clinical acinetobacter isolates from UMMC / Deepa Anbazhagan - Anbazhagan, Deepa (2012)
Quorum sensing is a term that describes an environmental sensing system that allows bacteria to monitor their own population density. Many gram negative bacteria use N-acyl-homoserine lactones (AHLs) as autoinducing quorum sensing signal molecules. This cell-density dependent regulation of gene expression contributes significantly to the size and development of the biofilm. Acinetobacter spp. are now emerging as important nosocomoial pathogens and it has been shown that they form biofilms with enhanced antibiotic resistance. In this study, we sought to find out if the biofilm formation among clinical isolates of Acinetobacter spp. is under the control of autoinducing quorum sensing molecules. We have also evaluated various quorum quenching strategies which can be used to attenuate the pathogenicity of these organisms. Biofilm formation among clinical isolates of Acinetobacter spp. was assessed and the production of signal molecules were detected with Chromobacterium violaceum CV026 biosensor system. Characterisation of autoinducers was carried out by thin layer chromatography bioassay followed by mass spectrometric analysis. An autoinducer synthase gene, abaΙ was identified among the isolates that produce quorum sensing signal molecules. The abaI gene was cloned, a mutant of abaI gene was created, and the biofilm forming capability of the mutant abaI gene was analysed. The quorum quenching property of the extracts from two soil isolates with a strong AHL-inactivating enzyme activity and the plant extracts of Phyllanthus spp., garlic bulb and lemon on clinical Acinetobacter spp. isolates was elucidated. Using a microtitre-plate assay it was shown that 60% of the 50 Acinetobacter spp. isolates significantly formed biofilms. Chromobacterium violaceum CV026 biosensor system detected the production of long chain AHLs among seven of these biofilm forming isolates. Thin layer chromatography bioassay and mass spectrometric analysis revealed that five of these isolates produced N-decanoyl homoserine lactone and two isolates produced acyl-homoserine lactone with a chain length equal to C12. The abaΙ gene was identified and it was shown that there was considerable inhibition in biofilm formation in the abaI::Tc mutant. Further, two soil isolates of the genus Bacillus with a strong AHL-inactivating enzyme activity were identified and the extracts from these soil bacilli was used to inhibit the biofilm forming capabilities of quorum sensing signal molecule producing clinical isolates of Acinetobacter spp. The quorum quenching properties of Phyllanthus spp. extracts, garlic bulb and lemon on the clinical Acinetobacter spp. isolates have also been reported. These data are of great significance as the signal molecules aid in biofilm formation which in turn confer various properties of pathogenicity to the clinical isolates including drug resistance. The use of quorum sensing signal blockers to attenuate bacterial pathogenicity is therefore highly attractive, particularly with respect to the emergence of multi antibiotic resistant bacteria. The results also showed that the extracts were capable of inhibiting the biofilm formation and also degrade the AHLs produced by these clinical isolates of Acinetobacter spp. Our results indicate that the AHLs -inactivation approach represents a promising strategy for prevention of diseases in which virulence is regulated by quorum sensing.